Global stability boundary analysis and verification of aviation pressure servo-controlled actuator system - Zhipeng Huang; Xinjie Li; Zeyu Cao; Chentian Ma; Yunhe Wang; Bin Yu; Guoliang Ma; Xiangdong Kong (Scientific Reports)
Abstract In this paper, the mathematical model of the aviation pressure servo valve controlled actuator system(APSVCAS) considering nonlinearity is established based on a jet pipe pressure servo valve in this article. And the dynamic characteristics and stability boundary of APSVCAS are analyzed, which provides theoretical guidance for the actual composition and the determination of parameters. Firstly, a jet-tube two-stage pressure servo valve for aviation hydraulic system is designed, and an accurate model of APSVCAS is established considering multiple nonlinear factors. Meantime, the influence of 34 parameters on the dynamic characteristics of the system is analyzed by using the second-order sensitivity analysis method. And the key parameters that significantly affect the dynamic characteristics of the system are extracted. Based on this, the system stability discrimination method is proposed from the perspectives of frequency domain and time domain, and the stability boundary of key parameters is obtained. Finally, the theoretical analysis results are verified on the experimental platform of APSVCAS. The experimental results show that the mathematical model of APSVCAS considering nonlinearity has satisfactory accuracy. Concomitantly, it is verified that the parameters’ stability boundary condition based on the sensitivity analysis method meet the stable output effect of the system under multiple working conditions.